Willing to have, willing to help, or ready to own—Determinants of variants of stewardship social practices around Blue-Green Infrastructure in dense urban communities - Lamond, Jessica; Everett, Glyn (Frontiers in Water, 2023)
There is increasing acceptance of the desirability of involving communities in stewardship activities around urban blue-green infrastructure (BGI) to generate acceptance, reduce vandalism and decrease the maintenance burden on authorities. However, little is known about the willingness of communities to engage in stewardship, or the drivers to participate in such activities. This research adopted a practice lens and firstly defined three variants of BGI stewardship associated with passive acceptance, active care for and ownership of BGI. Secondly, the research conceptualized these practices within a complex of pro-environmental practices communities could perform. Through a face-to-face household survey in a dense UK urban area, the research sought to identify the prevalence of these variants of practice, their associations with other pro-environmental practices and the meanings, resources and competencies that drive a household’s willingness to engage. The research found different willingness for the three variants with passive most popular and ownership least. Meanings associated with BGI stewardship practice appeared to differ in crucial respects from other pro-environmental practices and were most associated with water-management rather than climate concern, however some place-based motivations were also involved. Practical resource and competency considerations also affected willingness to perform active stewardship and ownership variants. The research concluded that promoting the water-management aspects of BGI for all variants, along with facilitation of engagement with more active variants, could increase participation in BGI stewardship.